2022
DOI: 10.3390/agronomy12102306
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Peaches for Brown Rot Resistance in Embrapa

Abstract: Brown rot, caused by Monilinia spp., is the main stone fruit disease. Major efforts to detect sources of resistance are being applied by several breeding programs worldwide. The main objective of this study was to seek sources of brown rot resistance, as well as to study the segregation, estimate the heritability, verify the possible existence of the maternal effect, and estimate the genetic advances. For this purpose, 20 parents and 303 seedlings, representing 16 breeding families, and ‘Bolinha’ (control) hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thus, it is targeted by institutional research groups searching for molecular markers of resistance; the FruitBreedomics (Europe) and the RosBREED (North American) projects were the most important collective initiatives thus far [11,12]. The main challenge in genetic improvement is that BR resistance is quantitatively inherited [13][14][15], so its heritability is medium to low with a high environmental influence, resulting in small and slow progress [10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is targeted by institutional research groups searching for molecular markers of resistance; the FruitBreedomics (Europe) and the RosBREED (North American) projects were the most important collective initiatives thus far [11,12]. The main challenge in genetic improvement is that BR resistance is quantitatively inherited [13][14][15], so its heritability is medium to low with a high environmental influence, resulting in small and slow progress [10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the Bolinha peach variety, from Brazilian origin, presents a good resistance mechanism with less susceptibility to brown rot than other varieties [35]. It has been observed that the resistance to disease of 'Bolinha' [22,33] and other resistant sources [36,37] is transmitted to their descendants. Following this approach, in our laboratory, we have selected peach genotypes from a population derived from the cross of two commercial varieties, 'Babygold 9 × 'Crown Princess', based on their tolerance to M. laxa and their quality.…”
Section: Introductionmentioning
confidence: 99%